PERILAKU REMAJA TERHADAP NILAI-NILAI KEAGAMAAN (STUDI DI DESA BETUNG KECAMATAN SEMENDAWAI BARAT KAB. OKU TIMUR-SUMATERA SELATAN) - Lidiawati Lidiawati (Fakultas Dakwah dan Komunikasi, 2017)
The problem of teenagers or young age groups in facing the challenges of their future has been paying central attention and research. The Progress achieved by the society in the physical or material field has not run linearly with the achievement in the field of social and religious. The main values of society including religious’ values are generally declining. In the social and religious spheres such as education, hajj, and prayer with the progress achieved do not seem having any significant improvement implications. Moreover, in certain areas of social and religious values which is embraced by society are not mostly looking displaced by global values, either directly from the consequences of development or the negative influence of the media.Adolescents sociologically are very vulnerable to external influences. It is because the search process of identity, so that it is easily vacillated and difficult to determine people who deserve to be cultivated. Teenagers at this age are very easy to interpret the trends that occur in society according to the truth of their own thinking. Adolescent’s behavior that is contrary to religious values seems uneasy to minimize as the development of modern technology. It is similarly to adolescents in rural areas that have been increasingly eroded by the current times. The adolescents who have faith, then the urge to commit evil will always be thwarted by their faith, because the commemoration of divine revelation is still into their mental attitude. The strong understanding about the three basic values in Islam that is Aqidah, Worship and Morals will affect the experience of these three basic values in the life of adolescents, both vertical relationships with Allah swt. and horizontal relatioship with human beings.